Using a blend of oilseed meals in the diets of Nile tilapia (Oreochromis niloticus): effects on the growth performance, feed utilization, intestinal health, growth, and metabolic-related genes - Ahmed A. Badran; Fawzy I. Magouz; Amr I. Zaineldin; Safaa E. Abdo; Asem A. Amer; Mahmoud S. Gewaily; Mahmoud A.O. Dawood (BMC Veterinary Research)
Abstract In this study, Nile tilapia were fed a blend of oilseed meals (BOM) that includes cottonseed meal (CSM), linseed meal (LSM), sesame meal (SSM), and sunflower meal (SFM) at a ratio of 1 CSM: 1 LSM: 1 SSM: 1 SFM. Six diets were formulated where the first diet included FM and SBM as protein sources and considered the positive control diet (FM). Another five FM-free diets were formulated, where SBM was substituted with BOM and included at 0, 100, 200, 300, and 400 g/kg diet. After 90 days, the FBW, WG, and PER were markedly increased while FCR decreased by FM-based diet and BOM at 0, 100, or 200 g/kg compared to fish-fed BOM at 300, and 400 g/kg (P < 0.05). The groups treated with BOM at 100–200 g/kg demonstrated considerable impairments, followed by those treated with BOM at 300 g/kg. Furthermore, fish given BOM at 400 g/kg had significantly less intestinal histological characteristics than the other groups. The relative expression of the IGF-1, GHR1, FABP, and CCK genes were downregulated in tilapia-fed BOM at 200, 300, and 400 g/kg compared to fish-fed FM-based diet (P < 0.05). The relative cost of feed per kg fish gain showed 4.42, 7.11, 8.14, 10.32, and 8.10% reduction rates in fish-fed SBM, or BOM at 100, 200, 300, and 400 g/kg. In conclusion, dietary BOM can be incorporated in Nile tilapia diets at up to 200 g/kg without affecting growth performance or feed utilisation. High inclusion levels (300 and 400 g/kg) may impair growth performance and feed utilisation by disrupting intestinal histological characteristics and reducing expression of growth and metabolic genes (GHR1, IGF-1, FABP, and CCK) in the liver.